The paradox of open innovation in Slovenian firms - Daša Farčnik; Tjaša Redek; Sonja Šlander (Prometheus)
Innovation and open innovation are expected to strengthen firm performance. The learning process and inbound activities are particularly important for catch-up countries and firms. The empirical evidence, though, is incomplete and provides inconclusive results. This paper studies the role of open innovation activities in a sample of Slovenian firms. Using a combination of survey data and official registry financial statements data, we investigate the differences in the role of open innovation across firms with different productivity. The results show that open innovation is more important in less productive firms. This is consistent with the theoretical ideas that stress the role of learning, capacity building and knowledge transfer. However, these firms also invest less in open innovation activities, which is a paradox in itself, introducing an important challenge for managers as well as questions for future research.